Love’s Weakness: Simone Weil and the Truthful Encountering of Others - Ens, Gerald (My University, 2017)
This thesis provides a presentation and analysis of Simone Weil’s articulation of the weakness of love vis-à-vis our encounters with others. It does so both as a way to better examine Christian theological claims about the importance of weakness and as a way of accessing the tensional depths of Simone Weil’s work from an often neglected angle. To achieve this engagement, I read Weil alongside Jean Vanier, whose life and work share with Weil a profound emphasis on the centrality of weakness for meeting others truthfully and lovingly. In Chapter One I draw on both Weil and Vanier to present their shared critique of relationships that are reduced to a pursuit of power and influence over others. I call such relationships “territorial” because they posit human beings as competitors for two-dimensional territory and therefore envision human relationships in essentially competitive terms. Chapter Two is a detailed presentation of Weil’s constructive work on the weakness of love that emphasizes her account of the impersonal, non-egoistic, and unattached relationships we ought to pursue with others. Weil claims that we experience the fullness of reality through an uncompromising embrace of all things, which we can only accomplish through the removal of ourselves in the face of others. We get concrete development of these themes in Weil’s presentation of neighbour love and friendship, which she understands as a total openness to another’s position, circumstance, and being. In the third chapter, I use the theme of communion in Vanier’s work to call into question the way Weil demands our total surrender to the other. I suggest that an absent self cannot be truly weak and vulnerable before others. The central problem, I suggest, is a conception in which any sort of positive presence is necessarily an obstacle and any imposition of oneself necessarily competitive.
Keywords: Simone Weil, Jean Vanier, Christian theology, theology of weakness, love, others and otherness, truthfulness, ethics, epistemology, vulnerability, embodiment, neighbour love, friendship, compassion